Shifts in rhizosphere fungal community during secondary succession following abandonment from agriculture - Hannula, S Emilia; Morriën, Elly; de Hollander, Mattias; van der Putten, Wim H; van Veen, Johannes A; de Boer, Wietse (The ISME Journal, 2017)
Activities of rhizosphere microbes are key to the functioning of terrestrial ecosystems. It is commonly believed that bacteria are the major consumers of root exudates and that the role of fungi in the rhizosphere is mostly limited to plant-associated taxa, such as mycorrhizal fungi, pathogens and endophytes, whereas less is known about the role of saprotrophs. In order to test the hypothesis that the role of saprotrophic fungi in rhizosphere processes increases with increased time after abandonment from agriculture, we determined the composition of fungi that are active in the rhizosphere along a chronosequence of ex-arable fields in the Netherlands. Intact soil cores were collected from nine fields that represent three stages of land abandonment and pulse labeled with 13 CO 2 . The fungal contribution to metabolization of plant-derived carbon was evaluated using phospholipid analysis combined with stable isotope probing (SIP), whereas fungal diversity was analyzed using DNA-SIP combined with 454-sequencing. We show that in recently abandoned fields most of the root-derived 13 C was taken up by bacteria but that in long-term abandoned fields most of the root-derived 13 C was found in fungal biomass. Furthermore, the composition of the active functional fungal community changed from one composed of fast-growing and pathogenic fungal species to one consisting of beneficial and slower-growing fungal species, which may have essential consequences for the carbon flow through the soil food web and consequently nutrient cycling and plant succession.